Carrier frequency estimation method of time-frequency overlapped signals based on cyclic correntropy spectrum - Tianshuang QIU; Xing CHEN; Jitong MA; Jingchun LI; Rong LI (Tongxin xuebao)
According to the performance degradation problem of the carrier frequency estimation method of time-frequency overlapped BPSK signals in Alpha-stable distribution noise,a novel carrier frequency estimation algorithm of the time-frequency overlapped BPSK signals based on the cyclic correntropy spectrum was proposed.The relationship between cyclic frequency and carrier frequency on the zero frequency section of the cyclic correntropy spectrum was deduced,which could be utilized for carrier frequency estimation.The proposed method can suppress the impulse noise and has better estimation performance than that of the contrastive methods.Simulation results are presented to demonstrate the effectiveness and robustness of the proposed method.